2007
DOI: 10.1007/s11095-007-9287-3
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake of Cationic Polymer-DNA Complexes Via Caveolae Plays a Pivotal Role in Gene Transfection in COS-7 Cells

Abstract: Purpose. Knowledge about the uptake mechanism and subsequent intracellular routing of non-viral gene delivery systems is important for the development of more efficient carriers. In this study we compared two established cationic polymers pDMAEMA and PEI with regard to their transfection efficiency and mechanism of cellular uptake. Materials and Methods. The effects of several inhibitors of particular cellular uptake routes on the uptake of polyplexes and subsequent gene expression in COS-7 cells were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
167
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(182 citation statements)
references
References 50 publications
12
167
0
1
Order By: Relevance
“…If PEI has higher affinity for these components than for the DNA the transfection efficiency decreases (Godbey et al 1999). Polyplexes with an overall positive charge bind to the cell surface through electrostatic interactions with negatively charged membrane lipids (van der Aa et al 2007) but are also responsible for increasing cell death (Tousignant et al 2000). However, reducing the ± charge ratio of the complexes reduces the transfection efficacy (Plank et al 1996) and therefore we defined the critical level of free PEI for efficient PEI/DNA for our medium/host system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If PEI has higher affinity for these components than for the DNA the transfection efficiency decreases (Godbey et al 1999). Polyplexes with an overall positive charge bind to the cell surface through electrostatic interactions with negatively charged membrane lipids (van der Aa et al 2007) but are also responsible for increasing cell death (Tousignant et al 2000). However, reducing the ± charge ratio of the complexes reduces the transfection efficacy (Plank et al 1996) and therefore we defined the critical level of free PEI for efficient PEI/DNA for our medium/host system.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the existence of several different endocytic pathways their own specific characteristics need to be taken into account (Khalil et al 2006). Cationic lipids with positive net charge on the surface bind to the cell by electrostatic interactions with negatively charged membrane components (van der Aa et al 2007), destabilize lipid bilayers and thus enable the DNA to escape (Wattiaux et al 1997). Wrobel and Collins (1995) were first to demonstrate the fusion between cationic liposomes and endocytic vesicles in cell cultures, but still both, the exact mechanism of the endosomal membrane crossing (Zuhorn et al 2005) and the DNA transfer across the nuclear membrane remain unidentified (Escriou et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…64 Similarly, PEI and pDMAEMA polyplexes have been found to be internalized in COS-7 cells via clathrin-and caveolin-dependent routes, though only the clathrin-mediated route is transfection-competent. 76 These observations do not suggest differing abilities to escape the same intracellular compartment in different cell lines but rather reflect the ability of complexes to escape from endosomes and lysosomes but not caveosomes. Furthermore, these results highlight the interdependency of the cellular processes involved in effective transfection.…”
Section: Endosomal Escape: Escape To the Cytosolmentioning
confidence: 83%
“…[225] Caveolae are subdomains of glycolipid rafts and are internalized via a common, clathrin independent, dynamin dependent, and cholesterol sensitive pathway. [226] They are around 50-80 nm in diameter and can constitute approximately a third of the plasma membrane area of the cells of some tissues, and are especially abundant on the surface of endothelial and in smooth muscle cells. Interestingly, multicaveolar assemblies can be observed, where many caveolae are connected together.…”
Section: Clathrin-mediated Endocytosis (Cme) Is Crucial For Intercellmentioning
confidence: 99%
“…[219] Entry of the polyplexes into the cell seems to occur mostly by unspecific as well as clathrinand caveolae-dependent endocytosis, but the mechanism is still not completely elucidated, since the uptake pathway seems to vary for different cell and polyplex types. [138] Van der Aal et al reported that uptake of pDMAEMA and PEI polyplexes in COS-7 cells is mediated via different uptake routes, including both the clathrin-and caveolae-mediated pathway, [226] whereas Gabrielson et al have shown that successful PEI-mediated gene delivery proceeds via an unspecific process. [227] However, size, charge density, flexibility, and amphiphilicity, as well as the structure can have an influence on the endocytoic pathway.…”
Section: Clathrin-mediated Endocytosis (Cme) Is Crucial For Intercellmentioning
confidence: 99%